ITERATIVE ANALISIS PADA KEPUASAN PENGGUNA UNTUK WEBSITE CROWDFUNDING DONASI DI INDONESIA - Heru Wijayanto Ariandono; Agnes Jocelyn (JURNAL ILMIAH BETRIK, 2022)
TheUtopia is a social enterprise startup or social business company that combines the basic concept of trading, which is seek profit with our obligation to help the social environment, TheUtopia provides a fundraising platform to help donors to make donations easily and safely. The purpose of this study is to analyze the level of satisfaction of website users so that co-authors can use the data to develop websites. The research model used is the DeLone & Mclean model. This research uses quantitative and qualitative methods. The results of quantitative research stated that users were dissatisfied with the website because the system quality, information quality and service quality had no effect on user satisfaction while the qualitative results stated that users were satisfied with the features provided by the website but the appearance of the website was too rigid and simple so it is not attractive to users.